Secure and duplication detection in cloud using cryptographic hashing method - Periasamy, J. K.; Latha, B. (International Journal of Engineering and Technology, 2018)
De-duplication systems are adopting De-duplication strategies such as client side or server side De-duplication.Particularly, in the beginning of cloud storage, data De-duplication techniques happen to add importance to store original volumes of data in the cloud. This technique motivates the enterprise and organization to farm out data storage to cloud service providers, as proof of several case studies was done.Block level de-duplication is used to discover, removes redundancies compare with previously stored information. The file will be separated into smaller segment as given by the system size or uneven size blocks or chunks whatever we need. Using predetermined size of blocks, the system can simplify the computations of block limits, although using uneven size blocks provides improved de-duplication. Secure Cloud introduce a new concept to audit entities with continuation of a Map Reduce cloud, which is used to help the client is easy to make data tags before feeding the data and audit with theprobity of data is analysed and stored in the cloud. the subject of previously finished work is fixed so that the computational load at user or auditor has huge amount of tag making. In accumulation, Secure Cloud also enables secure de-duplication. Perceive that the â€œvalidityâ€ measured in Secure Cloud is the deterrence of leakage, the side channel information. In order to check the leakage of such side channel data, the work accept the custom and design a proof of rights protocol amid cloud servers and clients, which permit clients to confirm the cloud servers what they exactly own the object information.